Asymmetrical conversations: contestations, circumventions, and the blurring of therapeutic boundaries - Naraindas, Harish; Quack, Johannes; Sax, William Sturman (Epistemologies of healing, 2014)
Medicines of the imagination : cultural phenomenology, medical pluralism, and the persistence of mind-body dualism / Laurence J. Kirmayer -- Porous dividuals? complying to a healing temple (Balaji) and a psychiatric out-patient department (OPD) / Johannes Quack -- Medical individualism and the dividual person / Francis Zimmermann -- My vaidya and my gynecologist : agency, authority, and risk in quest of a child / Harish Naraindas -- Davaa and duaa : negotiating psychiatry and ritual healing of madness / Helene Basu -- A healing practice in Kerala / William Sax and Hari Bhaskar -- Ayurveda in Britain : the twin imperatives of professionalisation and spiritual seeking / Maya Warrier